2015
DOI: 10.1088/0004-637x/801/2/143
|View full text |Cite
|
Sign up to set email alerts
|

DOES THE PRESENCE OF PLANETS AFFECT THE FREQUENCY AND PROPERTIES OF EXTRASOLAR KUIPER BELTS? RESULTS FROM THEHERSCHELDEBRIS AND DUNES SURVEYS

Abstract: The study of the planet-debris disk connection can shed light on the formation and evolution of planetary systemsand may help "predict" the presence of planets around stars with certain disk characteristics. In preliminary analyses of subsamples of the Herschel DEBRIS and DUNES surveys, Wyatt et al. and Marshall et al. identified a tentative correlation between debris and the presence of low-mass planets. Here we use the cleanest possible sample out of these Herschel surveys to assess the presence of such a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 85 publications
4
72
1
Order By: Relevance
“…In fact, additional evidence of the correlation between the presence of dust, low-mass planets, and lower stellar metallicities has been recently found by Marshall et al (2014). However, we caution that there are several biases that might prevent us from finding a clear statistically significant correlation (Moro-Martín et al 2015).…”
Section: Abundance Patterns and The Presence Of Discs And Planetsmentioning
confidence: 68%
See 1 more Smart Citation
“…In fact, additional evidence of the correlation between the presence of dust, low-mass planets, and lower stellar metallicities has been recently found by Marshall et al (2014). However, we caution that there are several biases that might prevent us from finding a clear statistically significant correlation (Moro-Martín et al 2015).…”
Section: Abundance Patterns and The Presence Of Discs And Planetsmentioning
confidence: 68%
“…Further analysis of the Herschel data by Marshall et al (2014) in a sample of 37 solar-type exoplanet hosts reveals a correlation between the presence of dust, low-mass planets, and low stellar metallicities. However, the detailed statistical analysis of 204 FGK stars by Moro-Martín et al (2015) does not find evidence of debris discs being more common around lowmass planet hosts, although the authors caution about possible contamination of the control sample by possible undetected low-mass planets and relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 95%
“…Bryden et al (2009) found little correlation between planet hosts and detection of an IR excess (the typical age of stars in their sample was ∼6 Gyr, whereas the stars in our sample are significantly younger). More recently, Moro-Martín et al (2015) examined a large (>200 star) sample of Herschel-observed stars to look for correlations between the presence of a debris disk and: (1) the presence of low-mass planets, (2) the presence of high-mass planets, (3) metallicity, and (3) the presence of one or more stellar companions. Even with their large sample size, Moro-Martín et al (2015) found no significant correlations between any of the aforementioned parameters.…”
Section: Planet Stirringmentioning
confidence: 99%
“…If the composition of the star reflects the composition of the planet-forming disk, one explanation could be that the dust grains that eventually build up the planetesimals are more easily formed in an environment enriched in heavier elements. The picture is far from clear, however, since a correlation with host star metallicity is observed for gas giants, but not for small exoplanets (Buchhave et al 2014) or for the tracers of planetesimal formation known as debris disks (Greaves et al 2006;Wyatt et al 2007;Moro-Martín et al 2015).…”
Section: Introductionmentioning
confidence: 97%